Lifetime - Frings, M.S. author. aut Link
XVIII, 248 p.
Keywords: In comparison to Husserl and Heidegger, Max Scheler's philosophy of time as first presented here, is considerably wider in scope. Using posthumous manuscripts, Frings shows that Scheler conceived the origin of time in the self-activating center of individual and universal life as threefold "absolute" time of a four-dimensional expanse. This serves as a basis for establishing the phenomenon of objective time in multiple steps of constitutionality, including the physical field theory and theory of relativity. For Scheler, objective time, even though anchored in absolute time, deserves "maximum attention" in a technological society. Frings focuses here with Scheler on time experience of values and among social groups, time experiences in the mind-set of capitalism, in politics and morals, in population dynamics, and time experiences in the process of aging, all of which were signposts in Scheler's thought before his early demise.